Asia in the global stage - Herrera Vinelli, Lorena (2020)
The Department of International Relations (National University, Costa Rica), has dedicated its academic efforts to reflect in 2020 on the transition or “return” of the world order to the Asian region, which is considered one of the main trends that characterize the XXI century.